Energy-oriented joint optimization of machine maintenance and tool replacement in sustainable manufacturing. (April 2021) - Xia, Tangbin; Shi, Guo; Si, Guojin; Du, Shichang; Xi, Lifeng
Highlights: We propose an energy-oriented joint optimization of machine maintenance and tool replacement policy. Energy consumption mechanisms and joint maintenance opportunities are integrated. The effects of the tool wear progression is modelled in a machine-tool system. The machine-tool PR model dynamically balances the cost-efficiency and the energy-efficiency. The policy reduces the total non-value-added energy consumption in sustainable manufacturing. Abstract: With the increasing attention on sustainable manufacturing, operation and maintenance (O&M) management focuses on not only budget limit, but also energy saving. For modern CNC systems, besides the energy consumption to operate and maintain the machine, a majority of energy consumption generated from tool wear should be considered. It means both machine degradation and tool wear are required to be modelled for the global saving energy. Thus, this paper proposes an energy-oriented joint optimization of machine maintenance and tool replacement (EJMR) policy by integrating energy consumption mechanisms and joint maintenance opportunities in a machine-tool system. The key issue is to combine the preventive maintenance (PM) scheduling of the machine and the polish/preventive replacement (PR) optimization of sequential tools to form energy-effective schemes. Therefore, joint maintenance opportunities of PM actions are utilized to perform tool polish/PR based on energy consumption mechanisms. Four successive procedures (energy consumption analysis, energy-oriented PM scheduling, machine-tool PR model and integrated decision-making process) are developed. Thereby optimal intervals of machine PM and tool polish/PR are obtained to save energy. The case study illustrates that compared with conventional maintenance policies, this proposed EJMR policy can significantly reduce the total non-value-added energy consumption (TNVE) in sustainable manufacturing.